The Utility of a Point-of-Care Transcranial Doppler Ultrasound Management Algorithm on Outcomes in Pediatric Asphyxial Out-of-Hospital Cardiac Arrest – An Exploratory Investigation - Lin, Jainn-Jim; Kuo, Hsuan-Chang; Hsia, Shao-Hsuan; Lin, Ying-Jui; Wang, Huei-Shyong; Hsu, Mei-Hsin; Chiang, Ming-Chou; Chan, Oi-Wa; Lee, En-Pei; Lin, Kuang-Lin (Frontiers in Medicine, 2022)
Abstract Background: Transcranial Doppler ultrasound is a sensitive, real time tool used for monitoring cerebral blood flow; it could provide additional information for cerebral perfusion in cerebral resuscitation during post cardiac arrest care. The aim of the current study was to evaluate the utility of a point-of-care transcranial Doppler ultrasound management algorithm on outcomes in paediatric asphyxial out-of-hospital cardiac arrest. Methods: This retrospective cohort study was conducted in two tertiary paediatric intensive care units between January 2013 and June 2018. All children between 1 month and 18 years of age with asphyxial out-of-hospital cardiac arrest and a history of at least 3 minutes of chest compressions, who were treated with therapeutic hypothermia and survived for 12 hours or more after the return of circulation were eligible for inclusion. Results: Twenty-one patients met the eligibility criteria for the study. Sixteen (76.2%) of the 21 children were male, and the mean age was 2.8±4.1 years. Seven (33.3%) of the children had underlying disorders. The overall 1-month survival rate was 52.4%. Twelve (57.1%) of the children received point-of-care transcranial Doppler ultrasound. The 1-month survival rate was significantly higher (p=0.03) in the point-of-care transcranial Doppler ultrasound group (9/12, 75%) than in the non-point-of-care transcranial Doppler ultrasound group (2/9, 22.2%). Conclusions: Point-of-care transcranial Doppler ultrasound group was associated with a significantly better 1-month survival rate compared with no point-of-care transcranial Doppler ultrasound group in paediatric asphyxial out-of-hospital cardiac arrest.